Social Capital, Internet Use and Poverty in West Java Province - Bayu Kharisma; Sutyastie Soemitro Remi; Adhitya Wardhana; Yudha Hadian Nur (Muhammadiyah University Press, 2021)
Social capital is important because it represents the productive benefits of sociability. The importance of social capital cannot be understated since it relates to every benefit of living in a society rather than as a hermit. Meanwhile, the internet, as a mode of rapid communication, may free the individual from family ties and open opportunities to join new cultures and communities. Since the end of the last century, information and communication technologies (ICTs), and the internet in particular, have been considered essential in providing access to markets, decreasing transaction costs, and increasing income for a significant proportion of people living in developing countries. This paper aims to investigate the effect of bonding and bridging social capital, internet use on poverty in West Java Province. The data used in this study was sourced from the Central Statistics Agency (BPS) of West Java Province in 2014, namely the National Socio-Economic Survey covering 26 districts/cities analyzed through order logit model. The results showed that social capital and internet use had a negative effect on poverty in West Java.